Slovak Republic : 2010 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
The economy is emerging from a deep recession. The downturn has, however, exacerbated the unemployment problem. The authorities and IMF staff agreed that the recession represents a permanent loss of potential output and lower potential growth. Relatively sound fiscal policies in the pre-crisis period helped contain the deficit and bring down the public debt. The financial sector is weathering the global financial crisis generally well. Unemployment and its regional dispersion are a major concern. The share of workers with higher education is low.